Postpartum pituitary necrosis: A report of 2 autopsy cases (Indian Journal of Case Reports, 2020)
Major hormonal changes emerge during pregnancy. The pituitary gland is one of the most affected organs with altered anatomy and physiology. Sheehan’s syndrome also known as Simmonds’s syndrome or postpartum anterior pituitary necrosis is due to ischemic necrosis secondary to blood loss and hypovolemic shock after child birth. We report two autopsy cases of postpartum anterior pituitary necrosis with their clinical correlation. Histopathological examination of pituitary in both the cases showed extensive areas of coagulative necrosis involving the anterior pituitary. Both the cases were associated with indirect causes of maternal deaths like infectious etiology.